Effect of pre-conception serum vitamin D level on pregnancy outcomes in women undergoing in vitro fertilization with fresh embryo transfer: a retrospective analysis - Aaron H. Y. Chan; Jennifer K. Y. Ko; Raymond H. W. Li; Tat On Chan; Ernest H. Y. Ng (Reproductive Biology and Endocrinology)
Abstract Background This study aims to investigate the association of pre-conception vitamin D levels on adverse pregnancy outcomes in women undergoing in vitro fertilization with fresh embryo transfer. Methods This was a retrospective cohort study using archived serum 25-hydroxyvitamin D measured in the pre-conception period before ovarian stimulation in patients undergoing in vitro fertilization with fresh autologous embryo transfer. A total of 306 women were included and adverse pregnancy outcomes in their resulting pregnancy were recorded. Patients who were vitamin D deficient (< 20ng/ml) were compared with those who were non-deficient (≥20ng/ml) and analysed for any association with adverse pregnancy outcomes. Results A total of 16/306 (5.3%) patients had hypertensive disorders of pregnancy (gestational hypertension and/or pre-eclampsia). The adjusted odds ratio for hypertensive disorders of pregnancy using vitamin D deficiency as a reference was 0.190 (95% CI 0.042–0.852) (p = 0.030). Other pregnancy complications were not significantly different with regards to pre-conception vitamin D status. Conclusions Pre-conception vitamin D deficiency is associated with an increased risk of hypertensive disorders in pregnancy in women undergoing in vitro fertilization with fresh embryo transfer. Trial registration HKUCTR 2361 (9th March 2018).